(untitled) (Development Service Industry Management, 2025)
The article substantiates the theoretical and practical foundations of implementing innovative HR strategies in the personnel management system of enterprises in the event industry, tourism and hospitality business. It identifies the growing importance of human capital as a key factor in ensuring the competitiveness and sustainability of organizations operating in conditions of post-war recovery, digital transformation, and labour market instability. The study emphasizes that traditional approaches to staff development no longer meet the dynamic requirements of modern service industries, where flexibility, creativity, and cross-functional cooperation define success. Particular attention is paid to skilling-methodologies – upskilling, reskilling, and cross-skilling – which represent a new paradigm of personnel development based on continuous learning, internal mobility, and the acquisition of hybrid competencies. The research outlines the distinctive features of each strategy: upskilling as vertical professional growth and adaptation to technological change; reskilling as horizontal movement and retraining within the organization; cross-skilling as the formation of multifunctional, interchangeable teams that strengthen internal communication and corporate synergy. It is proven that their integrated use contributes to reducing staff turnover, building a sustainable talent pool, improving motivation, and forming a positive organizational climate. The implementation of skilling strategies enhances productivity, loyalty, and innovation potential of employees, while creating a flexible and adaptive HR system capable of responding to market challenges. The paper concludes that the combination of upskilling, reskilling, and cross-skilling forms a synergistic effect, which ensures strategic resilience, competitive advantage, and long-term sustainable development of event, tourism, and hospitality enterprises in a period of global transformations.